PROFILE OF PUBLIC SCHOOL CHILDREN AND ADOLESCENT LIFESTYLES IN THE MUNICIPALITY OF MUÇUM - RS (Fiep Bulletin - online, 2014)
The present explorative-descriptive study is aimed at characterizing the lifestyle of fundamental Elementary students, aged 10 to 17, of public schools in Muçum - RS. The subjects of the study are 165 students, 100 from the State Secondary School General Souza Doca and 65 from the Municipal Fundamental School Jardim Cidade Alta. For data collection, we utilized the inventory Lifestyle - EVIA. The results show us that the lifestyles of the municipal and state school subjects are, in general, similar in almost all items surveyed, and activities that stand out are the ones carried out at home (watch TV, listen to music, talk/play with friends, study and help with domestic chores); Activities that are of note outside the home include talk/play with friends, play soccer, go cycling, walk and go for a drive. The most cited sports materials are related to cycling, soccer, volleyball and skating. The most used venues for sports activities and leisure are the home backyard, the street, sports or recreational clubs, field or barren plots. As for cultural activities, religious services, school activities during the off-school time and dance groups predominate. Our conclusion is that the cultural activities, leisure and sports are little diversified, and the activities, in general, signal a trend for sedentary life.
Keywords: lifestyle; living habits; children and adolescents